General Anesthesia as a Multimodal Individualized Clinical Concept - Rogobete, Alexandru Florin; Sandesc, Dorel (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In this book, a series of modern multimodal monitoring techniques during general anesthesia are presented, with a focus on patient-oriented anesthesia based on the individual needs of each patient reflected in the degree of hypnosis, the nociception-antinociception balance, and neuromuscular transmission. Moreover, a series of secondary implications for hemodynamic status, post-anesthetic recovery, and patient satisfaction are highlighted.